Contribution of nicotinamide as an intracyclic N dopant to the structure and properties of carbon dots synthesized using three α-hydroxy acids as C sources. (21st May 2022) - Mao, Zhen; Li, Hui; Gan, Na; Suo, Zili; Zhang, Huan; Zhao, Qiang
Abstract: Fixed carbon source and different dopants are mainly used to study the effect of heteroatoms on the structure and properties of carbon dots (CDs). As reactants, some dopants with conjugated structure and high nitrogen content may have important contributions to the structure and properties of doped CDs in addition to providing heteroatoms. Herein, to study the effect of fixed dopant on the structure and properties of CDs, three different CDs were synthesized using nicotinamide (NAA) and three common α -hydroxy acids (4–5 carbon atoms), and the optimal conditions were determined by orthogonal experimentation. Transmission electron microscopic micrographs showed that the average size of CDs based on nicotinamide are relatively large, up to 19.40 nm. X-ray photoelectron spectroscopy and Fourier-transform infrared spectroscopy demonstrated that these CDs have graphite nitrogen and several functional group structures. Ultraviolet–visible absorption spectra, fluorescence emission spectra, and fluorescence lifetime illustrated that these CDs have similar emission centers (460–470 nm) and fluorescence processes. The influence of carbon source on the surface structure of CDs was determined by systematically analyzing the response of these CDs in different pH ranges. DFT calculations revealed the distribution characteristics of the electrons in the excited state at the HOMO and LUMO energy levels of CDs. All the above characterizations and calculations proved that NAA is a desirable dopant with an important contribution to the structure and properties of CDs.